Functional and Structural Characterizations of Lytic Polysaccharide Monooxygenase, Which Cooperates Synergistically with Cellulases, from Ceriporiopsis subvermispora - Nguyen, Huyen; Kondo, Keiko; Yagi, Yusei; Iseki, Yu; Okuoka, Nagi; Watanabe, Takashi; Mikami, Bunzo; Nagata, Takashi; Katahira, Masato (ACS sustainable chemistry & engineering, 2022)
Lignocellulose-degrading fungi use various oxidative enzymes to degrade lignocellulosic biomass. Oxidative cleavage of cellulose by AA9 family lytic polysaccharide monooxygenases (LPMOs), LPMO9s, reportedly enhances cellulose depolymerization catalyzed by hydrolytic enzymes. To improve this enhancement, functional and structural understanding of LPMO9s is needed. Here, we recombinantly expressed an LPMO9 of Ceriporiopsis subvermispora, CsLPMO9, in Pichia pastoris. Simultaneous treatment of microcrystalline cellulose with CsLPMO9 and a commercial cellulase cocktail led to an 8.5-fold higher reducing sugar yield over the sum of the yields on individual treatment with CsLPMO9 and the cellulase cocktail. Similarly, simultaneous treatment of phosphoric acid-swollen cellulose resulted in a 3.2-fold increased yield. We also solved the crystal structure of CsLPMO9. CsLPMO9 takes on a typical LPMO structure having a β-sandwich fold with a copper-coordinating histidine brace. Solvent-exposed residues, including Tyr residues, in the putative substrate-binding surface of CsLPMO9 were deduced to be involved in binding cellulosic substrates. Mutagenesis of two characteristic Tyr residues revealed that they contribute to the affinity of CsLPMO9 with cellulosic substrate. The high synergy of CsLPMO9 and the cellulase cocktail may be promising for efficient biomass utilization.